Role-induced bias in criminal prosecutions - Anthonioz, Nicole Egli (European journal of criminology, 2019)
There are two main models of criminal prosecution in the western world. One tasks an independent magistrate (the examining judge) with the duty of conducting the investigation of a given case and transferring all evidence collected to the parties and the trial court. The other vests the prosecution with the task of conducting the investigation before representing the accusation in court. In 2011, a new code of criminal procedure entered into force in Switzerland, forcing most Swiss cantons to transition from the first model to the second. We investigate whether the change in the person conducting the investigation (from examining judge to prosecutor) could introduce or exacerbate bias against or in favor of the defendant. Through an empirical study carried out with students, we tried to determine whether this change might affect the fairness of the proceedings. We contend that the rights of the defense are better safeguarded in the first model than in the second, even if the contrast is not as stark as was initially predicted.